Biological soil crusts decrease infiltration but increase erosion resistance in a human-disturbed tropical dry forest - Szyja, Michelle; Felde, Vincent J. M. N. L.; Lückel, Sara; Tabarelli, Marcelo; Leal, Inara R.; Büdel, Burkhard; Wirth, Rainer (Frontiers in Microbiology, 2023)
Under continuous human disturbance, regeneration is the basis for biodiversity persistence and ecosystem service provision. In tropical dry forests, edaphic ecosystem engineering by biological soil crusts (biocrusts) could impact regeneration by influencing erosion control and soil water and nutrient fluxes, which impact landscape hydrology, geomorphology, and ecosystem functioning. This study investigated the effect of cyanobacteria-dominated biocrusts on water infiltration and aggregate stability in a human-modified landscape of the Caatinga dry forest (NE Brazil), a system characterized by high levels of forest degradation and increasing aridity. By trapping dust and swelling of cyanobacterial filaments, biocrusts can seal soil surfaces and slow down infiltration, which potentially induces erosion. To quantify hydraulic properties and erosion control, we used minidisc-infiltrometry, raindrop-simulation, and wet sieving at two sites with contrasting disturbance levels: an active cashew plantation and an abandoned field experiencing forest regeneration, both characterized by sandy soils. Under disturbance, biocrusts had a stronger negative impact on infiltration (reduction by 42% vs. 37% during regeneration), although biocrusts under regenerating conditions had the lowest absolute sorptivity (0.042 ± 0.02 cm s−1/2) and unsaturated hydraulic conductivity (0.0015 ± 0.0008 cm s−1), with a doubled water repellency. Biocrusts provided high soil aggregate stability although stability increased considerably with progression of biocrust succession (raindrop simulation disturbed: 0.19 ± 0.22 J vs. regenerating: 0.54 ± 0.22 J). The formation of stable aggregates by early successional biocrusts on sandy soils suggests protection of dry forest soils even on the worst land use/soil degradation scenario with a high soil erosion risk. Our results confirm that biocrusts covering bare interspaces between vascular plants in human-modified landscapes play an important role in surface water availability and erosion control. Biocrusts have the potential to reduce land degradation, but their associated ecosystem services like erosion protection, can be impaired by disturbance. Considering an average biocrust coverage of 8.1% of the Caatinga landscapes, further research should aim to quantify the contribution of biocrusts to forest recovery to fully understand the role they play in the functioning of this poorly explored ecosystem.